The ethical aspects of health research - Roopa Sidde Gowda; M S Rani (Wolters Kluwer Medknow Publications, 2012)
Ethics is a system of moral principles that not only applies values and judgments to medical practice, but also to any research that deals with human participants. Before pursuing any research, it is mandatory for a researcher to have some basic information about the ethics and ethical guidelines. Hence, the purpose of this review article is to give a brief insight into the ethics and ethical guidelines to Biomedical Research.